Family As a Condition of the Mental Health of a Child When Adapting To a Modern Kindergarten - Shabas, S (KnE Life Sciences, 2018)
This paper considers the family as the basic condition for the mental health of a child when adapting to kindergarten. The specific features of the intrafamilial conditions and factors shaping the mental health of a preschool child are shown. Scientific data on the regularities of a child’s passage through the adaptation period and the important role of the family for the dynamics of the adaptation process are provided. Analysis of empirical evidence of long-term interaction with families of pupils attending kindergartens of the Leninsky District of Ekaterinburg served to find out the influence of new social relations on the emotional well-being of a child and its parents upon admission to kindergarten. The intrafamilial problems deteriorating the psychophysical health of a child and complicating its adaptation to kindergarten are revealed. It is shown that these problems lead to emotional instability, developmental delay, as well as the troubled behavior and communication of a child. The peculiarities of how the adaptation period affects the parents are considered when parents reassess their attitude towards parenthood and their child in the process of the social assessment and new social conditions. The specific activities of the teaching staff when interacting with the child’s family members for the sake of maintaining and strengthening the child’s mental health are outlined. An analysis of the various forms and techniques of communication between teachers and specialists of preschool institutions dedicated to the psychological and pedagogical support of the family for raising the psychological awareness of parents is provided. The participation of parents in the interaction with teachers encourages their further active interaction, and such an active participation forms the background for maintaining and strengthening the mental health of a child while adapting to kindergarten. Keywords: family, mental health, adaptation to kindergarten.